Spirituality development: A study on awareness and effectiveness of spirituality trainings among youth - Abd. Wahab, Norazlina; Maamor, Selamah; Abd Ghani, Abdullah; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Elias, Nor Hanim; Nik Abdullah, Nik Safiah (Akademia Baru, 2017)
The aim of this study is to highlight the needs to enhance the spirituality development of youth. Although spirituality has been associated with a myriad of positive outcomes in both adults and youth, the importance of these constructs has not been reflected by social behaviour of the society. There were reported that a number of social crime and cases still occurs. This study relies mainly on primary data based on a convenient basis of youth in every district in Kedah. The study reveals the awareness and effectiveness of spirituality trainings among youth in Malaysia. The findings of this study may have policy ramifications towards enhancing spirituality among youth in Malaysia.